Is it possible to define the concept of Italianity? - Gałkowski, Artur; Ozimska, Joanna; Cola, Ilario (Sperimentare ed esprimere l’Italianità: Aspetti linguistici e glottodidattici, 2021)
Italianity is a very complex concept and for this reason its definition is not easy. In this essay the authors try to highlight these complexities and to provide a possible definition of Italianity that distinguishes or completes existing ones. However, before reaching this definition it is necessary to take into account also the false myths, ideals or prejudices that Italianity carries with it both in Italy and abroad, between Italians and foreigners, between Italophiles and Italics. Therefore, the article also highlights some “uncomfortable” data of the Italian spirit that is normally underestimated or poorly highlighted, concerning the less noble aspects of the Italian reality both in the past and in the present. Since Italy is a very varied country, geographically, historically, culturally and linguistically, this variety has also produced differences within the Bel Paese with lacerations and strong contrasts. Talking about Italianity also involves talking about these contrasts, “abnormalities”, sometimes real paradoxes, which are not modern phenomena but had already been recorded and reported through the centuries by authoritative Italians and foreigners. Listening to these voices together with the re-proposal of historical events that Italians have experienced allows the authors to reflect and face the Italian reality through a constant process of analysis and synthesis, of approach and estrangement. Only after this process of “purification” will it be possible to speak with greater détente about Italy, the Italian language and Italians as constituent elements of the Italian spirit.